Thiopyrano[2,3-d]Thiazoles as New Efficient Scaffolds in Medicinal Chemistry - Anna Kryshchyshyn; Olexandra Roman; Andrii Lozynskyi; Roman Lesyk (MDPI AG, 2018)
This review presents the up to date development of fused thiopyranothiazoles that comprise one of the thiazolidine derivatives classes. Thiazolidine and thiazolidinone-related compounds belong to the widely studied heterocycles from a medicinal chemistry perspective. From the chemical point of view, they are perfect heterodienes to undergo hetero-Diels–Alder reaction with a variety of dienophiles, yielding regio- and diastereoselectively thiopyranothiazole scaffolds. The annealing of thiazole and thiopyran cycles in condensed heterosystem is a precondition for the “centers conservative” creation of the ligand-target binding complex and can promote a potential selectivity to biotargets. The review covers possible therapeutic applications of thiopyrano[2,3-d]thiazoles, such as anti-inflammatory, antibacterial, anticancer as well as aniparasitic activities. Thus, thiopyrano[2,3-d]thiazoles may be used as powerful tools in the development of biologically active agents and drug-like molecules.